Analysis of the Importance of Inculcating Nationalism and Anti-racism Values on Multicultural Education for Generation Z in Indonesia - Demeiati Nur Kusumaningrum; Laura Adhisty; Dhania Eka Putri; Wirda Muzayyana (Journal of Islamic World and Politics, 2022)
This research aimed to analyze any approaches to prevent racism for the Indonesian Z generation. The youth generation must take attention to the issue of racism due to prevent the past experiences dealing with (1) the discrimination against the right of indigenous people and slavery in the era of Dutch colonialism; (2) the disharmony in the era of Old Order by the problem of Chinese and political participation, and (3) Papuanese propaganda as the instrument of external powers. By living in the digital era, the rapid access to information and economic transaction massively brought transnational ideas and values that challenge nationalism and nation-building. It used the interpretive method of research analysis. Data collecting used DOAJ by selected social sciences and political sciences categories to find the discourse of anti-racism among academicians. Data analysis was obtained from the literature review by mapping the case study and best practices for strengthening nationalism for Z generation. It was verified by the result of group discussion in SMA 1 Muhammadiyah Malang in 2019 and SMA Aisyiyah Boarding School Malang as the purposive sampling of Muslim teenagers. This research examines anti-racism rising after the internationalization of white supremacism in the 2016 U.S. administration. Racism as a transnational issue relates to the context of imperialism, islamophobia, and human right. Digital literacy by emphasizing multicultural education and nationalism is preferably based on a study in Indonesia. NU and Muhammadiyah support government policies as the two largest Muslim organizations in Indonesia.